2020
DOI: 10.1002/adtp.202000170
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Fluorescence/Photoacoustic Agent with an Intensifying Optical Performance for Imaging‐Guided Effective Photothermal Therapy

Abstract: Near-infrared fluorescent agents generally exhibit typical push-pull electron characteristics, and their optical behaviors are closely related to their molecular structures. Benzobisthiadiazole moiety as a classic electron acceptor has been typically used to design the Donor-Acceptor-Donor (D-AD) type of fluorescent/photoacoustic agents with emission in the second near-infrared window. In this work, two strategies are examined to intensify their absorption/fluorescence and fluorescence/photoacoustic imaging pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 113 publications
(22 reference statements)
1
14
0
Order By: Relevance
“…In comparison to the TPA, the N , N -dimethyl group has a stronger electron-donating capability . To further extend the NIR emission of the AIE materials, we attempted to modify the molecular structure.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In comparison to the TPA, the N , N -dimethyl group has a stronger electron-donating capability . To further extend the NIR emission of the AIE materials, we attempted to modify the molecular structure.…”
Section: Resultssupporting
confidence: 69%
“…In comparison to the TPA, the N,N-dimethyl group has a stronger electron-donating capability. 60 To further extend the NIR emission of the AIE materials, we attempted to modify the molecular structure. On the one hand, the N,N-dimethyl group was employed to enhance the electron-donating ability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…(3) Commonly used photoinduced electron transfer (PeT) and Förster resonance energy transfer (FRET) mechanism face challenges in the NIR-II region . (4) There was no organic fluorophore reported with >1200 nm emission maximum until last several months. , Therefore, it is not only highly demanded but also very challenging to develop a strategy that can flexibly modulate the emission wavelength and then construct long-emission activatable probes based on a stable and water-soluble fluorophore.…”
mentioning
confidence: 99%
“…Hongsg roup developed BBTD-1302 (7k)b y employing 3,4-ethylenedioxythiophene-containing bithiophene and styrene as the conjugating bridge,a nd N,Ndimethylamino groups as electron donors. [82] Theoretical calculations revealed intramolecular charge transfer (ICT) from the N,N-dimethylamino groups to the BBTD core and ab and gap of 0.88 eV,w hich afforded longer-wavelength maximum absorption/emission at 942/1302 nm. Results indicated that the styrene bridge and the N,N-dimethylamino electron donor in the design of NIR dyes can effectively induce red-shifted absorption/emission.…”
Section: Donor Modificationmentioning
confidence: 99%